2017
DOI: 10.1002/adv.21886
|View full text |Cite
|
Sign up to set email alerts
|

A study of dielectric behavior of manganese doped barium titanate–polyimide composites

Abstract: In this work, a series of BaTi 1−x Mn x O 3 -polyimide films were prepared by simple solution casting method. For the preparation of composite films firstly, manganese doped barium titanate, BaTi 1−x Mn x O 3 (where x = 0.00, 0.01, 0.03, 0.05) was synthesized by sol-gel process. The effect of Mn doping on its structural and dielectric properties was nicely explained. The highest dielectric constant value of 7,104 was obtained for BaTi 0.99 Mn 0.01 O 3 (BTMn) nanoparticles with low dielectric loss value 2.44. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…These peaks were appeared as a result of complete thermal imidization of nanocomposite thin films. Our previous research work showed the similar data for the pure polyimide thin film …”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…These peaks were appeared as a result of complete thermal imidization of nanocomposite thin films. Our previous research work showed the similar data for the pure polyimide thin film …”
Section: Resultssupporting
confidence: 75%
“…The X‐ray diffractograms of BTL/PI nanocomposite thin films are displayed in Figure . Like pure polyimide, a hump was observed in all the prepared nanocomposite thin films at around 19° (2θ value). X‐ray diffraction pattern revealed that there was no any sharp peak for nanocomposite thin films, which implies that all the prepared films were amorphous in nature .…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…This region serves well for tunable microwave device applications due to the associated high dielectric constant and low losses . However, utilization of BST in miniaturized multilayer structures is not frequent due to high dielectric loss (tan δ) in microwave region and the brittleness and rigidity of the ceramic .…”
Section: Introductionmentioning
confidence: 99%